Prediction of transient vibration response of dual-rotor-blade-casing system with blade off. (November 2019) - Wang, Nanfei; Liu, Chao; Jiang, Dongxiang
Fan blade off occurring in a running rotor of the turbofan engine dual-rotor system will cause a sudden unbalance and inertia asymmetry, which results in large impact load and consequently induces the rubbing between blade and casing. In order to reveal the transient dynamic response characteristics of actual aero-engine when fan blade off event occurs, the dynamic model of dual-rotor-blade-casing system is developed, in which the distribution characteristics of the stiffness and mass, the load transfer, and the coupling effects of dual-rotor and casing are included. Considering several excitations caused by blade off, the physical process and mechanical characteristics of the fan blade off event are described qualitatively. Considering that only the casing acceleration signal can be used for condition monitoring in actual aero-engine, the transient response including rotor vibration displacement and casing vibration acceleration during the instantaneous status are obtained. Due to the time-varying and highly nonlinear characteristics of vibration responses, frequency slice wavelet transform is employed to isolate the vibration signal features. The results show that the impact load induced by the sudden imbalance causes significant increase of vibration amplitude. The rubbing action between blade and rotor will impose constraint effects on the rotor, which decreases the transient vibration amplitude. The inertia asymmetry has a big impact on the transient response. The vibration characteristics of casing acceleration under blade off are similar to those of rotor displacement, while casing acceleration response attenuates to stable value faster and is more sensitive to high-frequency components of vibration.